The Influence of Islamic Law on the Development of Sharia Economics in Indonesia - Faisal, Muhammad Faisal; Alfad, Sahf Alfad (Alhamdulillah : Jurnal Agama Islam, 2023)
This study aims to analyze the influence of Islamic law on the development of sharia economics in Indonesia. By examining key sectors such as sharia banking, halal industry, and zakat distribution, this study shows that the application of Islamic legal principles, such as the prohibition of usury, transparency in transactions, and zakat management, has contributed significantly to the growth of the sharia economic sector. The results of the study show a significant increase in total assets of sharia banking, exports of halal products, and zakat management from year to year. Although this sector continues to grow, challenges in the broader integration of Islamic principles and public understanding of sharia economics still exist. Therefore, more in-depth policies and increased public understanding are needed to strengthen the sharia economic sector in Indonesia.